Molecular identification, biomass, and biochemical composition of the marine chlorophyte Chlorella sp. MF1 isolated from Suez Bay - Mostafa El-Sheekh; Mahmoud Abu-Faddan; Atef Abo-Shady; Mohamed Zein Alabedin Nassar; Wagdy Labib (Journal of Genetic Engineering and Biotechnology, 2020)
Abstract Background An Egyptian indigenous unicellular green microalga was isolated from the coastal water of Suez Bay (N 29.92°, E 32.473°), Red Sea, Egypt. The molecular analysis based on 18S rRNA sequence showed that the gene sequence for this strain was highly similar (100% identity and 98% query cover) to different Chlorella strains isolated from different habitats. Results The observed morphological characters together with the molecular phylogeny assigned the isolated microalga as Chlorella sp. MF1 with accession number KX228798. This isolated strain was cultivated for estimation of its growth and biochemical composition. The mean specific growth rate (μ) was 0.273 day−1. Both the biomass productivity and the cellular lipid content increased by increasing salinity of the growth medium, recording a maximum of 6.53 gDW l−1 and 20.17%, respectively, at salinity 40.4. Fourteen fatty acids were identified. The total saturated fatty acid percentage was 54.73% with stearic (C18:0), arachidic (C20:0), and palmitic acids (C16:0) as major components, while the total unsaturated fatty acid percentage was 45.27% with linoleic acid (C18:2c) and oleic acid (C18:1) as majors. Conclusion This algal strain proved to be a potential newly introduced microalga as one of the most proper options available for microalgae-based biodiesel production. The proximate analysis showed the protein content at 39.85% and carbohydrate at 23.7%, indicating its accessibility to various purposes.